Positive association between serum lactate dehydrogenase levels and blood pressure: evidence from NHANES 2015–2016 - Hu, Tao; Li, Linfeng; Cao, Qiqiang; Tu, Weiling; Huang, XianTao; Yuan, Tan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundSerum lactate dehydrogenase (sLDH) is an enzyme implicated in tissue injury and inflammatory responses. Despite its established role in these pathophysiological processes, the association between sLDH and blood pressure remains underexplored. The present findings suggest that sLDH could emerge as a valuable biomarker for blood pressure regulation and may hold significant promise in the management of hypertension.MethodsOur investigation utilized data from the National Health and Nutrition Examination Survey (NHANES) 2015–2016, comprising 3,469 participants after excluding those under the age of 20, individuals on antihypertensive therapies, and cases with incomplete data. sLDH levels were categorized into tertiles, while blood pressure measurements were conducted under standardized protocols. To elucidate the relationship between sLDH levels and blood pressure, multivariate regression analyses and smooth curve fitting techniques were employed, adjusting for 17 covariates, including age, sex, and body mass index.ResultssLDH corresponds with both systolic blood pressure (SBP) and diastolic blood pressure (DBP). The adjusted smooth curve fitting diagram demonstrates a linear positive connection between sLDH and SBP, with an increment of 0.053 mmHg (95% CI: 0.032, 0.074; p < 0.001) in SBP for every 1 U/L increment in LDH concentrations. The connection between sLDH and DBP is non-linear. sLDH concentrations below 123 U/L have a linear positive connection with DBP, increasing 0.079 mmHg (95% CI: 0.042, 0.115, p < 0.001). When sLDH concentrations exceed 123 U/L, there is not a substantial connection with DBP (P = 0.574).ConclusionOur study demonstrates a linear positive correlation between sLDH and SBP. A non-linear association was observed between sLDH and DBP, with a positive relationship for sLDH levels below 123 U/L. These findings underscore the potential of sLDH as a biomarker for blood pressure regulation.